Severe obesity in peruvian adolescents: analysis of the National Household Survey (ENAHO), 2009 - 2010 - Pajuelo Ramírez, Jaime (2019)
Introduction. Childhood obesity is a Public Health problem in our country; instead of that, the situation of population aged between 10-19 years-old has been poorly studied. Objective. To determine the prevalence of obesity and severe obesity in Peruvian adolescents. Methods. A secondary study of data from the National Household Survey 2009-2010. The Body Mass In ≥ dex (BMI) was used to define obesity as a BMI value 95 percentile. Severe obesity (SO) was defined using two criteria, BMI ≥ 99 p and 120% of the value corresponding to 95p of BMI. Results. 7,6% presented obesity, and 2,4 and 1,4% were diagnosed with SO according to the mentioned criteria. The highest prevalence of SO was evidenced in men (3% vs. 1,8%), age group of 10 to 14 years-old (3,4% vs. 2%), people who are living in Lima Metropolitana (4,2% vs. 2,4%), or in a urban area (3,2% vs. 1,9%), non-poor (3,1% vs. 1,9%) and in cities less than 1000 meters above sea level (3,5% vs. 2,1%). A higher prevalence ratio (PR) of SO was found in men and non-poor. Having an age between 15 to 19 years old, residing in the mountains or jungle, rural area and being poor, were independently associated with a lower PR. Conclusion. The prevalence of SO was low, with a predominance of men, in the 10 to 14 year old group, on the coast and Metropolitan Lima, in urban areas, in those considered non-poor and in those living below 1000 meters above sea level.